PENGARUH PENERAPAN DISIPLIN KERJA DAN PROFESIONAL TERHADAP KINERJA ANGGOTA POLRI PADA POLRES MALUKU TENGAH - Sulatry Sukidjan (Jurnal Cita Ekonomika, 2019)
This study aims to analyze and explain the application of work discipline, and professionally to the performance of Polri members at the Central Maluku Police in Masohi. This study took a sample of 200 members of the Indonesian National Police as respondents and used multiple linear regression analysis methods. The results of the study prove partially that the application of discipline with indicators following the workplace apples, attending work apples, knowing the work procedures that apply, are not permitted to leave work before work is completed, use work uniforms according to work days, use identification as long as they know the regulations, must provide a certificate when unable to, must obey the leader, must be prepared to accept the reward when guilty, get an award when completing a good job has a positive significant influence on the performance of members of the National Police. Professionals with indicators: providing services to the community in accordance with their expertise, in providing services to the community very understanding of the work provided, in providing services to the community very mastered the work provided, in providing services to the community very much in the field of knowledge, in providing services to the community without prioritizing family factors, in providing services to the community without prioritizing the factors of colleagues, providing services to the community always prioritizes the public interest, providing services to the community without discriminating ethnic groups, providing services to the community differentiating races has a significant positive effect on the performance of police officers at the Central Maluku Police in Masohi. For researchers and the following research, it needs to be developed in other institutions so as to increase references in discussing the support of research results.